A New Cross-Shaped Graphite Furnace with Ballast Body for Reduction of Interferences in Atomic Absorption Spectrometry - A. A. Asweisi; H. M. Kuss (E-Journal of Chemistry)
A new crossed graphite furnace for atomic absorption spectrometry (GFAAS) was designed and installed in heated graphite atomizer (HGA500) combined with Perkin-Elmer spectrometer (AAS1100). The Tungsten ballast body was inserted inside one part of the crossed furnace in a way perpendicular to light path. The analyzed sample was injected manually on the ballast body inside the cross and pushed into the measuring zone using the original inner and additional purge gas. The sample was adsorbed strongly on the ballast and evaporated and transferred with different rates at different temperatures during the temperature program allowing the separation of analyte and matrix signals. Analysis of middle volatile element such as copper and manganese in standard urine sample (seronorm 2525) showed complete separation of analyte and background signals with good sensitivity and repeatability.